Le numérique, simple mue du libéralisme ou avènement d’une économie soutenable - Marc Laget (Netcom)
The Information Society roots its central potential into the simplification of code writing and data transmission. This Tendency makes the immaterial economy prevail on material and energetic exchanges within the economic value creation process.